2021
DOI: 10.1002/mnfr.202100071
|View full text |Cite
|
Sign up to set email alerts
|

An Isolated Dose of Extra‐Virgin Olive Oil Produces a Better Postprandial Gut Hormone Response, Lipidic, and Anti‐Inflammatory Profile that Sunflower Oil: Effect of Morbid Obesity

Abstract: Introduction This study evaluates the effects of 25 mL of three types of oils [extra‐virgin olive oil (EVOO), olive oil (OO), and sunflower oil (SO)] on postprandial (3 h) satiety markers and variables related to metabolic status and inflammation in non‐obese patients (n = 6) and in those with morbid obesity (n = 6), before and 1 year after Roux‐en‐Y gastric by‐pass (RYGB). Methods and Results After EVOO intake, serum acylated ghrelin decreases and GLP1 increases more than with OO and SO. EVOO causes a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The most common fat sources for the majority of products were sunflower oil and rapeseed oil. It has been shown that sunflower oil induced an increase of different proinflammatory markers [ 45 ] and that intake of polyunsaturated fatty acids (PUFA-fatty acid identified in sunflower oil) was highest in vegans, followed by pescatarians, semi-vegetarians and vegetarians, and lowest in meat-eaters [ 46 ]. Even though the PBMAs showed a moderate fat content, overconsumption can lead to a diet high in fat which can be associated with unfavorable changes in gut microbiota, fecal metabolic profiles and plasma proinflammatory factors, which could have unfavorable consequences for long-term health outcomes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common fat sources for the majority of products were sunflower oil and rapeseed oil. It has been shown that sunflower oil induced an increase of different proinflammatory markers [ 45 ] and that intake of polyunsaturated fatty acids (PUFA-fatty acid identified in sunflower oil) was highest in vegans, followed by pescatarians, semi-vegetarians and vegetarians, and lowest in meat-eaters [ 46 ]. Even though the PBMAs showed a moderate fat content, overconsumption can lead to a diet high in fat which can be associated with unfavorable changes in gut microbiota, fecal metabolic profiles and plasma proinflammatory factors, which could have unfavorable consequences for long-term health outcomes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The similar glycemic and insulinemic responses after the consumption of oleocanthal-poor and oleocanthal-rich meals imply that the enrichment of olive oil with oleocanthal did not confer additional benefit compared to olive oils poor in oleocanthal. Previous studies have shown that EVOOs, compared to OOs, can lower postprandial hyperglycemia in patients with impaired fasting glucose [30], non-obese patients and those with morbid obesity after Roux-en-Y gastric bypass [31]. This effect was accompanied by higher insulin responses mediated by the ability of EVOOs to augment the secretion of incretins.…”
Section: Discussionmentioning
confidence: 94%
“…Another possible explanation of the link between EVOO, GLP-1 and the consequent glycaemic control, from a mechanistic point of view, derives from the study by Garcia-Serrano et al, which showed that the intake of EVOO produced favourable changes in GLP1 levels, resulting in greater postprandial GLP-1 concentrations when compared with olive oil and sunflower oil [ 88 ].…”
Section: Evoo Glp-1 and Glycaemic Control Improvement: Possible Under...mentioning
confidence: 99%